Ekokritiški pogled na poezijo Svetlane Makarovič - Badalič, Tanja (Jezik in slovstvo, 2016)
The article first briefly presents ecocriticism, as a discipline studying the relationship between literature and the physical environment, as well as the practice of ecocriticism, which encourages more ethical interaction with the world. In addition, the role of literature in generating a new ethical and ecological consciousness is stressed. The main focus is on an ecocritical view of Svetlana Makarovič's poetry, in order to determine the ethical and ecological message of her poetics. The article also deals with the author%s newspaper columns, which explicitly reveal her point of view on broader environmental issues.
Keywords: Makarovič, Svetlana, 1939-; slovenska poezija; ekokritika; antropocentrizem; ekocentrizem; ekološka funkcija književnosti; etična funkcija književnosti; literarne študije